Relationships Between Childhood Abuse and Eating Pathology Among Individuals with Binge-Eating Disorder: examining the Moderating Roles of Self-Discrepancy and Self-Directed Style. Issue 4 (4th July 2022) - Borg, Skylar L.; Schaefer, Lauren M; Hazzard, Vivienne M; Herting, Nicola; Peterson, Carol B; Crosby, Ross D; Crow, Scott J; Engel, Scott G; Wonderlich, Stephen A
ABSTRACT: Childhood maltreatment appears to increase the risk for eating disorders (EDs). The current study examined potential moderating factors (i.e., self-discrepancy and negative self-directed style), which may increase or decrease the impact of maltreatment (i.e., emotional abuse, physical abuse, sexual abuse) on later ED symptoms. One hundred seven men and women with binge-eating disorder (BED) completed semi-structured interviews and questionnaires assessing childhood maltreatment, self-discrepancy, negative self-directed style, and ED pathology. Linear regression was used to examine the moderating role of self-discrepancy and negative self-directed style in the associations between each type of abuse and level of ED severity. Actual:ought self-discrepancy (i.e., the difference between one's self and who one believes they ought to be) moderated the relationships between ED pathology and emotional abuse ( β  =.26 p =.007), as well as physical abuse ( β  =.23, p =.02). Results suggest that the relationship between childhood abuse (i.e., emotional abuse, physical abuse) and ED pathology may be stronger for those with higher levels of actual:ought self-discrepancy. Further clarification of the relationships between actual:ought self-discrepancy and distinct forms of childhood abuse is needed, as well as intervention studies examining whether targeting actual:ought self-discrepancy provides an additional benefit for trauma-exposed individuals with BED.